Leading and Working From Home in Times of COVID-19: On the Perceived Changes in Leadership Behaviors. (May 2022) - Stoker, Janka I.; Garretsen, Harry; Lammers, Joris
Due to the COVID-19 crisis, managers and employees in many organizations suddenly are forced to work from home. Although working from home (WFH) is not a new phenomenon, it is new in its current scale and scope because of COVID-19. Against this background, we investigate the effect of WFH during the COVID-19 crisis on changes in leadership behaviors, and associated changes in perceived manager quality and productivity, at different hierarchical levels in organizations. Based on the literature, we develop two predictions in opposite directions. On the one hand, implementing WFH may force managers to show less direction and control and especially more delegation. On the other hand, research into the effects of exogenous shocks such as COVID-19, suggests that managers may become more controlling and delegate less. Consistent with the first prediction, we find that managers perceive they execute significantly less control and delegate more. Employees also perceive a significant decrease in control, however they perceive on average no change in delegation. Furthermore, and in line with the second prediction, employees of lower-level managers even report a significant decrease in delegation. Finally, our results show that increased delegation is associated with increased perceived productivity and higher manager quality. Together, these results suggest that in the context of the COVID-19 crisis, the effectiveness of WFH might be hampered by the fact that required changes in leadership behaviors, in particular in delegation, are difficult to realize in times of crisis.